2021
DOI: 10.1183/16000617.0053-2021
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension phenotypes in patients with systemic sclerosis

Abstract: Pulmonary hypertension (PH) commonly affects patients with systemic sclerosis (SSc) and is associated with significant morbidity and increased mortality. PH is a heterogenous condition and several different forms can be associated with SSc, including pulmonary arterial hypertension (PAH) resulting from a pulmonary arterial vasculopathy, PH due to left heart disease and PH due to interstitial lung disease. The incidence of pulmonary veno-occlusive disease is also increased. Accurate and early diagnosis to allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 150 publications
0
41
0
Order By: Relevance
“…SSc associated-PAH (SSc-PAH) is considered WHO Group 1 PH and may be the result of direct remodeling of the pre-capillary pulmonary arterioles, or rarely be attributable to pulmonary veno-occlusive disease/pulmonary capillary hemangiomatosis (PVOD/PCH). It is a leading cause of mortality in SSc patients, with an incidence of 8–13% ( 12 , 13 ) and is more commonly associated with limited cutaneous systemic sclerosis (lcSSc) ( 14 ), Patients with SSc-PAH have a poor prognosis in comparison to SSc patients without PAH, with 3 year survival of only 52% ( 14 – 16 ). Several studies have demonstrated that the intrinsic RV dysfunction in SSc patients leads to worse outcomes in SSc-PAH in comparison to idiopathic PAH ( 2 , 13 , 17 ).…”
Section: Right Ventricular Dysfunction and Pulmonary Hypertensionmentioning
confidence: 99%
See 4 more Smart Citations
“…SSc associated-PAH (SSc-PAH) is considered WHO Group 1 PH and may be the result of direct remodeling of the pre-capillary pulmonary arterioles, or rarely be attributable to pulmonary veno-occlusive disease/pulmonary capillary hemangiomatosis (PVOD/PCH). It is a leading cause of mortality in SSc patients, with an incidence of 8–13% ( 12 , 13 ) and is more commonly associated with limited cutaneous systemic sclerosis (lcSSc) ( 14 ), Patients with SSc-PAH have a poor prognosis in comparison to SSc patients without PAH, with 3 year survival of only 52% ( 14 – 16 ). Several studies have demonstrated that the intrinsic RV dysfunction in SSc patients leads to worse outcomes in SSc-PAH in comparison to idiopathic PAH ( 2 , 13 , 17 ).…”
Section: Right Ventricular Dysfunction and Pulmonary Hypertensionmentioning
confidence: 99%
“…One year mortality for SSc-PAH has been found to be 30%, while one year mortality for those with idiopathic PAH is 15% ( 17 ). Mortality rates remain high despite therapy ( 14 ).…”
Section: Right Ventricular Dysfunction and Pulmonary Hypertensionmentioning
confidence: 99%
See 3 more Smart Citations